Penalty Method for Non-Stationary General Variational Like Inequalities - Salahuddin (Journal of Applied Nonlinear Dynamics, 2026)
We suggest a general variational like inequalities in an infinite dimensional space, where only approximation sequences are known instead of an exact value of the cost mapping and feasible set, and to apply a sequence of inexact solutions of auxiliary problems involving general penalty functions. Its convergence is attained without concordance of penalty, accuracy, and approximation parameters under certain coercivity type assumptions.